CRISPR Generated SIX6 and POU4F2 Reporters Allow Identification of Brain and Optic Transcriptional Differences in Human PSC-Derived Organoids - Wahlin, Karl J.; Cheng, Jie; Jurlina, Shawna L.; Jones, Melissa K.; Dash, Nicholas R.; Ogata, Anna; Kibria, Nawal; Ray, Sunayan; Eldred, Kiara C.; Kim, Catherine; Heng, Jacob S.; Phillips, Jenny; et al. (Frontiers in Cell and Developmental Biology, 2021)
Human pluripotent stem cells (PSCs) represent a powerful tool to investigate human eye development and disease. When grown in 3D, they can self-assemble into laminar organized retinas; however, variation in the size, shape and composition of individual organoids exists. Neither the microenvironment nor the timing of critical growth factors driving retinogenesis are fully understood. To explore early retinal development, we developed a SIX6-GFP reporter that enabled the systematic optimization of conditions that promote optic vesicle formation. We demonstrated that early hypoxic growth conditions enhanced SIX6 expression and promoted eye formation. SIX6 expression was further enhanced by sequential inhibition of Wnt and activation of sonic hedgehog signaling. SIX6+ optic vesicles showed RNA expression profiles that were consistent with a retinal identity; however, ventral diencephalic markers were also present. To demonstrate that optic vesicles lead to bona fide ‘retina-like’ structures we generated a SIX6-GFP/POU4F2-tdTomato dual reporter line that labeled the entire developing retina and retinal ganglion cells respectively. Additional brain regions, including the hypothalamus and midbrain-hindbrain (MBHB) territories were identified by harvesting SIX6+/POU4F2- and SIX6- organoids respectively. Using RNAseq to study transcriptional profiles we demonstrated that SIX6-GFP and POU4F2-tdTomato reporters provided a reliable readout for developing human retina, hypothalamus, and midbrain/hindbrain organoids.